The impact of two bacterial species and five aqueous plant extracts on yield and yield components of rice (Oryza sativa L.) and surof (Echinochloa crus-galli L.) - Musa Ebrahimpour; Pourang Kasraie; Hamid Reza Larijani; Hamid Reza Tohidi-Moghadam; Sahar Honarmand-Jahromy (SN Applied Sciences, 2023)
Abstract Chemical exudates from some plants to the environment have been reported as causative agents of adverse effect on growth of neighboring plants and thus affecting normal growth in their natural environment. The mode of action of Chemical exudates on plants is involves a large number of biochemical reactions. This research aimed to investigate the effect of foliar application of different levels of two bacterial species and five aqueous plant extracts on the yield and yield components of Oryza sativa L. and Echinochloa crus-galli L. This research was conducted as a factorial based on randomized complete block design (RCBD) with three factors with three replications during the 2017–2018 crop year. The main factor included aqueous extracts of Sorghum (Sorghum bicolor L. Moench), Broccoli (Brassica oleracea var. Italica), Nettle (Urtica dioica), Eucalyptus (Eucalyptus globulus Labill), Elderberry (Sambucus nigra L.), and Streptomyces sp-albos containing thaxtomin, Xanthomonas campestris, and control (without aqueous plant extracts and surfactant). The sub-factor includes foliar application treatment with different levels of zero (control), 5, 10, and 15% of extracts, and the third experimental factor included Oryza sativa L. and E. crus-galli L. The results indicated the plant height, leaf area index (LAI), grain yield, biological yield, chlorophyll a, chlorophyll b, total chlorophyll, and grain protein content decreased, and the grain starch content increased with increasing the extract concentration; the highest effect was obtained at 15% of extracts. The lowest value of leaf area index (3.13) were found in higher concentration of X. campestris followed by Elderberry extract (5%, 10% and 15%) and Nettle (10%) extracts. It was also found that using extract reduced yield characteristics and components of Oryza sativa L., E. crus-galli L., and Elderberry extract showed the highest negative effect. According to the results, Oryza sativa L. had higher plant height, LAI, grain yield, biological yield, harvest index, chlorophyll, grain protein content, and grain starch content than E. crus-galli L. In all extractions, control treatment had the highest number of panicles plant−1 in both plants (rice and E. crus-galli L., 260.1 and 117.1 mg g−1 FW). The results suggested that various extracts, especially Nettle, and 15% of Elderberry can control E. crus-galli L. at the germination stage under field conditions.